Severe Necrotizing Acute Pancreatitis: Does Percutaneous Drainage Save Lives? - Guzmán, Cristian A.; Quintero, Marco J.; Prada, Johan S.; García, Mara J. (Revista del Hospital Italiano de Buenos Aires, 2025)
Acute pancreatitis is an inflammation of the pancreas that destroys acinar cells. Its incidence has increased globally, primarily due to biliary lithiasis and alcoholism. This report describes a 58-yearold man with a history of alcoholism who developed acute pancreatitis after consuming fatty foods and alcohol. Initially managed conservatively, he developed complications requiring admission to the ICU. Computed tomography (CT) revealed multiple necrotic collections, managed by CT-guided percutaneous drainage. After five weeks, the patient showed significant improvement, allowing removal of the catheters and discharge with outpatient follow-up. This case highlights the “Step-Up Approach”, favoring minimally invasive techniques like percutaneous drainage over open necrosectomy in severe necrotizing pancreatitis, improving survival and reducing complications. Multidisciplinary management is essential to optimize clinical outcomes.